Akselerasi Pelayanan Publik Berbasis Digital Studi Kasus Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Belu - Joseph Franky Leto Bere; Fransiskus Atok; Graceana Elma Mau Buti (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The research objective is to describe the acceleration of public services at the One-Stop Integrated Services and Investment Service, by analyzing supporting and inhibiting factors and formulating a digital-based public service model. The research focus is collecting and exploring accurate, current and comprehensive data using interview, observation and documentation techniques. The research results show that there is a tendency (trend) to increase the performance of public service delivery in Belu Regency.